Two Cases of Ascending Aortic Intramural Hematoma Combined with Cardiac Tamponade Treated with Different Strategies - Kim, Min-Suk; Kim, Tae-Jin; Moon, Jong Joo; Nam, Jae-Hyung; Han, Dong-Hoon; Ahn, Ji-Hun; Kim, Tae-Hoon; Kim, Do-Hoi; Youn, Young-Nam; Kim, Yoon-Nyun (Soonchunhyang medical science, 2012)
Aortic intramural hematoma (IMH) is classically defined as a variation of aortic dissection where blood collects within the aortic media without the presence of an intimal flap. Ascending IMH is known to have worse clinical outcomes than IMH of the descending aorta or aortic arch. Therefore, some patients with higher risk of disease progression require surgical corrections. However, the indications and the benefits of surgical management of ascending IMH, compared with medical treatment only, have not yet been established. We present two cases of IMH in the ascending aorta that presented with cardiac tamponade; patients were treated differently according to risk factors. KCI Citation Count: 0